2018
DOI: 10.1080/21645515.2018.1480236
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to get vaccinated against Ebola: A mapping of Guinean people positions

Abstract: Objective: To map the different personal positions of Guinean people regarding vaccination against Ebola.Methods: From January to April 2016, 304 adults in Guinea were presented with 48 vignettes depicting situations in which getting vaccinated would be possible. These situations varied as a function of the constructs of health-protective behavior theories. The participants indicated the likelihood they would get vaccinated in each case.Results: Seven qualitatively different positions were found: Always Vaccin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 23 publications
0
11
0
1
Order By: Relevance
“…Always in Guinea, Kpanake et al . 42 found that 38% of participants said they were always ready to be vaccinated. Differences could be explained by study participants and the survey timing (before or during vaccination; before, during or after the epidemic).…”
Section: Discussionmentioning
confidence: 99%
“…Always in Guinea, Kpanake et al . 42 found that 38% of participants said they were always ready to be vaccinated. Differences could be explained by study participants and the survey timing (before or during vaccination; before, during or after the epidemic).…”
Section: Discussionmentioning
confidence: 99%
“…[17,28,20,22,25,3032,3638] In their study on why the Guinean people were vaccinated against Ebola. Kpanake et al [42] found a reluctance rate of 19%. This rate is a little low compared to the rates revealed by this systematic review.…”
Section: Discussionmentioning
confidence: 99%
“…In a national household survey in Guinea, Irwin et al [41] reported that 84.2% of participants said their family would accept Ebola vaccines. Always in Guinea, Kpanake et al [42] found that 38% of participants said they were always ready to be vaccinated. Differences could be explained by study participants and the survey timing (before or during vaccination; before, during or after the epidemic).…”
mentioning
confidence: 99%
“…A further example of this is the experience shared by Kpanake et al in this journal, on the hypothetical willingness of Guineans to be vaccinated against Ebola; with 25% of respondents not supporting vaccination, and a further 19% demonstrating hesitancy toward vaccination. 23 These findings were not dissimilar to 34% refusal rate of individuals offered the investigational Ebola vaccine during the ring-vaccination, effectiveness study undertaken in Guinea in 2016; which was attributed to mistrust of the Ebola surveillance team. Lessons learnt from this experience, need to be expanded upon for future epidemic and pandemic threats to ensure countries are adequately informed on how best to roll-out vaccines under such emergency situations.…”
mentioning
confidence: 85%